Correction: Synthesis of heteroleptic phosphine–copper(i) complexes: fluorescence sensing and catalytic properties. (15th June 2021) - Luo, Chen-Lin; Hu, Chu-Xing; Shang, Ping; Wen, Guan-Zhao; Zhu, Jia-Jun; Xuan, Ya-Hui; Xia, Bang-Lian; Liu, Yu-Chen; Jiang, Zi-Hao; Dong, Geng; Zhang, Wei; Gui, Liu-Cheng; et al.
Abstract : Correction for 'Synthesis of heteroleptic phosphine–copper(i ) complexes: fluorescence sensing and catalytic properties' by Chen-Lin Luo et al., New J. Chem., 2021, 45, 8910–8917, DOI: ; 10.1039/D0NJ06095J .